2015
DOI: 10.1179/1432891714z.0000000001070
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of mechanical properties of cementitious materials exposed to wet–dry cycles of sulphate solution

Abstract: In order to study sulphate attack effects on the mechanical behaviour of cementitious materials, the compressive behaviour of such materials subjected to wet-dry cycles of sulphate solution was investigated. Then, their variation of mass was recorded. According to the experimental results, it was observed that the mortars subjected to wet-dry cycles of sulphate attack were more severely damaged than ones immersed in a sulphate solution. In addition, these experimental results showed that the ultimate strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Through experiments, Robert et al [6] compared the volume expansion of concrete after soaking in sodium sulfate solution, the wet-dry circulation of sodium sulfate solution and the freeze-thaw cycle of sodium sulfate solution. The experiments showed that the volume expansion was the largest in the wet-dry cycle and that in the freeze-thaw cycle was the middle, in continuous immersion was the smallest, indicating that the wet-dry cycle has a very serious impact on the durability of the material.it was also observed through experiments that the mortars subjected to wet-dry cycles of sulphate attack were more severely damaged than ones immersed in a sulphate solution [7].…”
Section: Introductionmentioning
confidence: 50%
“…Through experiments, Robert et al [6] compared the volume expansion of concrete after soaking in sodium sulfate solution, the wet-dry circulation of sodium sulfate solution and the freeze-thaw cycle of sodium sulfate solution. The experiments showed that the volume expansion was the largest in the wet-dry cycle and that in the freeze-thaw cycle was the middle, in continuous immersion was the smallest, indicating that the wet-dry cycle has a very serious impact on the durability of the material.it was also observed through experiments that the mortars subjected to wet-dry cycles of sulphate attack were more severely damaged than ones immersed in a sulphate solution [7].…”
Section: Introductionmentioning
confidence: 50%
“…As depicted in Figure 9, the peak value of the variation of the mass of structural EPS concretes under sulfate attack in this study was 1.68%, which is much smaller than that of plain concrete (12%) under the same experiment conditions [40]. It was owing to the incorporation of EPS beads and fly ash, low water:binder ratio, and the choice of cement type designed in this study that made the structural EPS concrete have superior sulfate resistance and less weight variation than ordinary concrete.…”
Section: Resultsmentioning
confidence: 91%
“…However, in alternating dry and wet conditions, there is a dual corrosion of physical and chemical factors. Liao et al [33] studied the effects of sulfate erosion on the mechanical properties of mortar. The results showed that mortar suffered more severe damage under sulfate solution wet-dry cycles than when simply immersed in sulfate solution.…”
Section: Introductionmentioning
confidence: 99%